Computer-Aided Choosing of an Optimal Structural Variant of a Robot for Extracting Castings from Die Casting Machines - Ivo Malakov; Velizar Zaharinov; Stiliyan Nikolov; Reneta Dimitrova (Actuators, 2023)
In the present article, the solution for choosing the optimal structural variant of an industrial robot for extracting castings from die casting machines is considered. For this purpose, the process of extracting the castings from the mold is analyzed. On this basis, functions are defined, and a functional structure of the robot is built. Alternative variants of devices for each function are developed. The set of possible structural variants are constructed, considering the compatibility between devices and the possibility of performing more than one function with one device. The problem of choosing an optimal structural variant is formulated, and its characteristic features are determined. The main stages of a methodology and application software for the problem’s solution are presented. After an analysis of requirements for the extractor, the set of criteria for evaluating the structural variants are determined. The set includes criteria that minimize the production costs, production floor space, as well as the energy costs in the operation process, which is of particular importance in the conditions of global energy crisis. A mathematical model of the problem is built. The formulated multi-criteria optimization problem is solved, both with equal objective functions and with different priority.